Analysis and structural characterization of the vid-pisco market - Chiang Vegas, Marco Esteban (2025)
The objective of this was to determine the factors and social actors that characterize the vid-pisco market in Peru. Using a methodology with a non-experimental qualitative approach of exploratory and descriptive scope, a structural analysis was carried out with the support of a group of five experts familiar with the system studied and the Cross-Impact Matrix Multiplication Applied to a Classification tool. The findings allowed us to identify the most influential and dependent factors of the system: the number of people identified with the vid-pisco as a Peruvian symbol, the number of liters of pisco consumed per person, and the percentage of market growth per person per year. On the other hand, the most important social actors turned out to be tourists who visit the country and consume pisco, local consumers, and national distributors. The key factors are important for the system since good management of these favors its development; in the same way that the actions carried out by the actors would complement their development. This study constitutes a starting point for the planning and design of strategies that support the evolution of the system in the medium or long term.